Fluid inclusions - Roedder, Edwin, 1919- (Reviews in Mineralogy & Geochemistry, 2018)
Volume 12 of Reviews in Mineralogy introduces to fluid inclusions. It covers the folowing questions: when and where inclusions form. how they change, how to prepare material and make microthermometric measurementsl, how to interpret these data, and what has been found in applications of fluid-inclusion studies to each of a series of different geologic environments. This book also attempts to discuss the many applications of fluid inclusions to the study of and understanding of geologic processes and the geologic environments in which they acted.